Pengetahuan Ibu Hamil Tentang Hiperemesis Gravidarum di Rumah Sakit Umum Daerah Rokan Hulu - ., Andria (Jurnal Martenity and Neonatal, 2017)
Hyperemesis gravidarum described as nausea and vomiting in pregnancy cukupberat which could result in losing weight , dehydration , acidosis , the loss of his hydrochloride acid when vomiting .Incidence hyperemesis gravidarum based on the data darirekam medical rsud rokan upstream there are 480 the pregnant women of the months january 2015 - April 2016 are as many as 196 the pregnant women experienced hyperemesis gravidarum .This study aims to to see how knowledge pregnant women about hyperemesis gravidarum at RSUD Rokan Hulu .The kind of research this is a descriptive with the design research cross sectional .The outcome of research on 30 respondents, knowledgeable good as many as four people (13.3 %) , knowledgeable enough as many as 11 people (36.6 % and knowledgeable less from 15 people (50 %) .The research can be taken conclusion knowledge mother hami ltentang hyperemesis gravidarum is less at 15 respondents ( 50 % ).